Avaliação da dinâmica de portadores de carga em cerâmica multiferróicas por meio de espectroscopia dialétrica - Silveira, Luiz Gustavo Davanse da (2015)
In this work, temperature-dependent and frequency-dependent dielectric investigations have been performed in TbMnO3 ceramics processed in either oxygen or argon atmospheres The dieletric constant of both samples exhibited three anomalies in the temperature range between 12 and 300 K. Two anomalies occurred above 100 K and were atributed to the Maxwell-Wagner effect in grain boundaries and to hopping polarization in grain cores. Also, a strong correlation between dielectric properties and crystalline structure was observed. In the sample processed in oxygen atmosphere, the presence of manganese vacancies and the smaller unit cell allow the long range motion of charge carriers. In the sample processed in argon atmosphere, on the other hand, charge carriers have only short range motion. Also, in this sample the existance of inequivalent hopping probabilities was observed, which are a result of intrinsic factors like orbital ordering, bondig anisotropies, and Hund interaction Bellow 100 K a dielectric relaxation was observed. This relaxation follows the empirical Cole-Cole model and was attributed to small polaron tunnelling. X-ray photoelectrons spectroscopy was also conducted. The results showed that indeed the structural differences resulted in diferences between the electronic structure of the samples.